2018
DOI: 10.3126/nccj.v3i1.20253
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Financial Performance in Nepal

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
(9 reference statements)
2
12
0
Order By: Relevance
“…Bhattarai (2017) discover that board size has negative effect on financial performance of commercial banks in Nepal. The result also supported by study done by Lamichhane (2018) among Nepalese firms (seven commercial banks, seven development banks, five finance company, one trading company, two manufacturing, two hydropower, two hotels and four insurance companies) depict that board size is negatively related with ROA. This is according to organizational theory where boards with large number of members take comparatively longer time take to decisions (Steiner, 2007).…”
Section: Page40supporting
confidence: 67%
“…Bhattarai (2017) discover that board size has negative effect on financial performance of commercial banks in Nepal. The result also supported by study done by Lamichhane (2018) among Nepalese firms (seven commercial banks, seven development banks, five finance company, one trading company, two manufacturing, two hydropower, two hotels and four insurance companies) depict that board size is negatively related with ROA. This is according to organizational theory where boards with large number of members take comparatively longer time take to decisions (Steiner, 2007).…”
Section: Page40supporting
confidence: 67%
“…Management decisions automatically affect the firms' direction (Datta, 2018;Kamau, 2018). Decisions are therefore established on shareholding composition, financial prospects due to firms capabilities, corporate governance and arising economic factors on the market (Lamichhane, 2018). Financial distress is widely considered as various instances where firms encounter financial challenges.…”
Section: Introductionmentioning
confidence: 99%
“…chi-square, is used on the degree of freedom along with other goodness of fit indices, which include 1-Goodness of Fit Index (GFI) and 2-Adjusted Goodness of Fit Index (AGFI) and 3-Comparative Fit Index (CFI) and 4-Tucker-Lewis Index (TLI) and 5-Root Mean Square of Standardized Errors (SRMR) and 6-Root Mean Square Error of Approximation (RMSEA) whose value is less than 0.08 represents reasonable errors of approximation in the population. The goodness of fit indices of measurement models are reported separately in Table (5). It can be concluded that the model fit is suitable for the data, and the results can be reliable.…”
Section: The First Topic 2 Theoretical Principles and Hypothesis Deve...mentioning
confidence: 97%
“…Therefore, public confidence in the banking system must be maintained, which is crucial to the proper functioning of the banking sector and the economy as an authority. Therefore, it can be concluded that corporate governance in banks will greatly affect their performance, including the level of flexibility of banks (Bhattrai, 2017& Lamichhane, 2018 and the economy as an authority. Therefore, it can be concluded that banks' corporate governance will significantly impact their performance, including the level of banks' agility.…”
Section: ‫المصارف‬ ‫مرونة‬ ‫على‬ ‫اإلسالمية‬ ‫الصيرفة‬ ‫في‬ ‫الشركات‬...mentioning
confidence: 99%